190k views
4 votes
(5.3a−0.8)−(1.6−4.7a)=2a−(a−0.3)

User Sravanti
by
4.7k points

2 Answers

0 votes

Answer:

a = 0.3.

Explanation:

(5.3a−0.8)−(1.6−4.7a)=2a−(a−0.3)

5.3a − 0.8 − 1.6 + 4.7a = 2a − a + 0.3

5.3a + 4.7a - 2a + a = 0.3 + 0.8 + 1.6

9a = 2.7

a = 0.3.

User Qasim Ali
by
5.0k points
6 votes

Answer: a = 0.3

Explanation:

First, distribute(-1)

5.3a-0.8-1.6+4.7a=2a-(a-0.3)

Then, distribute(-1)

5.3a-0.8-1.6+4.7a=2a-a+0.3

Then, combine like terms

10a-2.4=a+0.3

Then, add(2.4)

10a=a+2.7

Then, subtract(a)

9a=2.7

Then, divide(9)

a = 0.3

Hope it helps <3

User LyphTEC
by
4.8k points